IGF-1 Haploinsufficiency Causes Age-Related Chronic Cochlear Inflammation and Increases Noise-Induced Hearing Loss - Adelaida M. Celaya; Lourdes Rodríguez-de la Rosa; Jose M. Bermúdez-Muñoz; José M. Zubeldia; Carlos Romá-Mateo; Carlos Avendaño; Federico V. Pallardó; Isabel Varela-Nieto (Cells, 2021)
Insulin-like growth factor 1 (IGF-1) deficiency is an ultrarare syndromic human sensorineural deafness. Accordingly, IGF-1 is essential for the postnatal maturation of the cochlea and the correct wiring of hearing in mice. Less severe decreases in human IGF-1 levels have been associated with other hearing loss rare genetic syndromes, as well as with age-related hearing loss (ARHL). However, the underlying mechanisms linking IGF-1 haploinsufficiency with auditory pathology and ARHL have not been studied. Igf1-heterozygous mice express less Igf1 transcription and have 40% lower IGF-1 serum levels than wild-type mice. Along with ageing, IGF-1 levels decreased concomitantly with the increased expression of inflammatory cytokines, Tgfb1 and Il1b, but there was no associated hearing loss. However, noise exposure of these mice caused increased injury to sensory hair cells and irreversible hearing loss. Concomitantly, there was a significant alteration in the expression ratio of pro- and anti-inflammatory cytokines in Igf1+/− mice. Unbalanced inflammation led to the activation of the stress kinase JNK and the failure to activate AKT. Our data show that IGF-1 haploinsufficiency causes a chronic subclinical proinflammatory age-associated state and, consequently, greater susceptibility to stressors. This work provides the molecular bases to further understand hearing disorders linked to IGF-1 deficiency.